De novo variants in RHOBTB2, an atypical Rho GTPase gene, cause epileptic encephalopathy. Issue 8 (25th May 2018) - Belal, Hazrat; Nakashima, Mitsuko; Matsumoto, Hiroshi; Yokochi, Kenji; Taniguchi‐Ikeda, Mariko; Aoto, Kazushi; Amin, Mohammed Badrul; Maruyama, Azusa; Nagase, Hiroaki; Mizuguchi, Takeshi; Miyatake, Satoko; Miyake, Noriko; et al.
Abstract: By whole exome sequencing, we identified three de novo RHOBTB2 variants in three patients with epileptic encephalopathies (EEs). Interestingly, all three patients showed acute encephalopathy (febrile status epilepticus), with magnetic resonance imaging revealing hemisphere swelling or reduced diffusion in various brain regions. RHOBTB2 encodes Rho‐related BTB domain‐containing protein 2, an atypical Rho GTPase that is a substrate‐specific adaptor or itself is a substrate for the Cullin‐3 (CUL3)‐based ubiquitin ligase complex. Transient expression experiments in Neuro‐2a cells revealed that mutant RHOBTB2 was more abundant than wild‐type RHOBTB2. Coexpression of CUL3 with RHOBTB2 decreased the level of wild‐type RHOBTB2 but not the level of any of the three mutants, indicating impaired CUL3 complex‐dependent degradation of the three mutants. These data indicate that RHOBTB2 variants are a rare genetic cause of EEs, in which acute encephalopathy might be a characteristic feature, and that precise regulation of RHOBTB2 levels is essential for normal brain function. Abstract : We identified three de novo RHOBTB2 variants in three patients with epileptic encephalopathies and acute encephalopathy (febrile status epilepticus). RHOBTB2 is a substrate‐specific adaptor or itself is a substrate for the CUL3‐based ubiquitin ligase complex. Transient expression experiments revealed that mutant RHOBTB2 was more abundant than wild‐type RHOBTB2, and co‐expression of CUL3 decreased the level of wild‐type RHOBTB2 but not the level of any of the three mutants, indicating impaired CUL3 complex‐dependent degradation of the three mutants.